Analysis of the Effect of Perception of Benefits and Perception of Risk on Interest in Using Online Loans with Ease of Use as a Moderating Variable on Ibm Asmi Students - Rudianto; Haichal Aufar Ardian; Jones Z. Rante (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of perceived benefits and perceived risks on the interest in using online loans with ease of use as a moderating variable on IBM ASMI Jakarta Students. The population and sample of this study were selected from a saturated sample of 100 people. The analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) 4.0. The results of the analysis show that perceived benefits have a positive effect on the interest in using SPayLater IBM ASMI Jakarta Students. The calculation results show that perceived benefits are proven to have a positive effect on interest in using. The T-statistic score of perceived benefits is 1.728, greater than 1.64. Perceived risk has a negative effect on interest in using SPayLater IBM ASMI Jakarta Students. The calculation results show that perceived risk has a negative effect on interest in using. The T-statistic score of perceived benefits is -0.202, less than 1.64. The variables ease of use and perceived benefits on interest in using SPayLater IBM ASMI Jakarta Students are significantly positive. This means that the ease of using SPayLater IBM ASMI Jakarta Students. On the other hand, the variable of risk perception towards the interest in using SPayLater of IBM Jakarta students is negative and not significant. This means that the ease of use factor cannot moderate the influence of risk perception on interest in using